A New Species of Saccharosydne Kirkaldy from Argentina (Hemiptera: Delphacidae) - Marino, Ana Maria (2010)
Saccharosydne is the most diverse genus of the tribe Saccharosydnini. Male, femaleand nymphal Saccharosydne have been captured in recent collections from garlic (Allium sativum),rye (Secale cereale) and pampas grass (Cortaderia spp.) in Argentina. In this contribution, we describeand illustrate a new species S. subandina sp. nov., adding information on the geographical distributionand host plants. Saccharosydne subandina can be distinguished from its congeners by the followingcombination of features: uniformly light green-yellowish color with a distinctive rounded blackmacula on both genae; vertex 1.5x longer than wide, and projecting beyond eyes almost one half of itslength; parameres divergent with internal and external angles acute; and dorsolateral angles of pygoferproduced caudad. A key for species identifi cation based on male genitalia and external morphology,is provided.